Nomenclature and semantic descriptions of ulcerative and inflammatory lesions seen in Crohn's disease in small bowel capsule endoscopy: An international Delphi consensus statement. Issue 1 (February 2020) - Leenhardt, Romain; Buisson, Anthony; Bourreille, Arnaud; Marteau, Philippe; Koulaouzidis, Anastasios; Li, Cynthia; Keuchel, Martin; Rondonotti, Emmanuele; Toth, Ervin; Plevris, John N; Eliakim, Rami; Rosa, Bruno; et al.
Background: In the medical literature, the nomenclature and descriptions (ND) of small bowel (SB) ulcerative and inflammatory (U-I) lesions in capsule endoscopy (CE) are scarce and inconsistent. Inter-observer variability in interpreting these findings remains a major limitation in the assessment of the severity of mucosal lesions, which can impact negatively on clinical care, training and research on SB-CE. Objective: Focusing on SB-CE in Crohn's disease (CD), our aim is to establish a consensus on the ND of U-I lesions. Methods: An international panel of experienced SB-CE readers was formed during the 2016 United European Gastroenterology Week meeting. A core group of five CE and inflammatory bowel disease (IBD) experts established an Internet-based, three-round Delphi consensus but did not participate in the voting process. The core group built illustrated questionnaires, including SB-CE still frames of U-I lesions from patients with documented CD. Twenty-seven other experts were asked to rate and comment on the different proposals for the ND of the most frequent SB U-I lesions. For each round, we used a 6-point rating scale (varying from 'strongly disagree' to 'strongly agree'). The consensus was reached when at least 80 % of the voting members scored the statement within the 'agree' or 'strongly agree' categories. Results: A 100% participation rate was obtained for all the rounds. Consensual ND were reached for the following seven U-I lesions: aphthoid erosion, deep ulceration, superficial ulceration, stenosis, edema, hyperemia and denudation . Conclusion: Considering the most frequent SB U-I lesions seen in CE in CD, a consensual ND was reached by the international group of experts. These descriptions and names are useful not only for daily practice and medical education, but also for medical research.